2017
DOI: 10.1038/srep46328
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics and Spatial-Temporal Clusters of Mumps in Shandong Province, China, 2005–2014

Abstract: Mumps presents a serious threat to public health in China. We conducted a descriptive analysis to identify the epidemiological characteristics of mumps in Shandong Province. Spatial autocorrelation and space-time scan analyses were utilized to detect spatial-temporal clusters. From 2005 to 2014, 115745 mumps cases were reported in Shandong, with an average male-to-female ratio of 1.94. Mumps occurred mostly in spring (32.17% of all reported cases) and in children aged 5 to 9 (40.79% of all reported cases). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
7
23
0
Order By: Relevance
“…However, two outbreaks occurred in 2006 and 2011. Similar phenomena can be observed in other parts of China [ 17 , 18 ]. Likely because of the periodic changes in the incidence of mumps.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, two outbreaks occurred in 2006 and 2011. Similar phenomena can be observed in other parts of China [ 17 , 18 ]. Likely because of the periodic changes in the incidence of mumps.…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, mumps cases were reported in all 12 months, but most occurred between April and July, with a small peak in October and January. This bimodal seasonal distribution was consistent with that of northern China [ 17 , 18 , 34 ] and prompts that there may be a relationship between the mumps incidence and the climate. A study in Guangzhou found that mean temperature, relative humidity, and atmospheric pressure can increase the risk of mumps, whereas wind speed has a protective effect [ 35 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…8 The present study findings with relation to month/season wise distribution of cases was similar to a study conducted by Li et al where maximum incidence of cases was found in spring season followed by Winter months. 12 The clinical findings of fever with parotid gland swelling was similar to a study conducted by Zamir et al where parotid gland swelling was found in 94.4% of cases and fever was found in 55% of cases. 13 The same findings were also found in a study conducted by Martina et al 14 The average duration of parotid gland swelling was 8 days in present study and this finding was comparable to a study conducted by Indranil et al where mean duration of swelling was 6.91±1.95 days.…”
supporting
confidence: 75%
“…The seasonable distribution of mumps has been detected in various areas, with the highest incidence occurring in spring (Park, 2015;Sane et al, 2014;Shah et al, 2006). However, the seasonal distribution varies between northern and southern China, with the peaks in spring and summer respectively (Li et al, 2017b;Liu et al, 2015;Yang et al, 2014a). Such distributions indicate that meteorological factors may impact on the transmission of mumps.…”
Section: Introductionmentioning
confidence: 99%